Assessing vector competence of mosquitoes from northeastern France to West Nile virus and Usutu virus. - Jean-Philippe Martinet; Chloé Bohers; Marie Vazeille; Hubert Ferté; Laurence Mousson; Bruno Mathieu; Jérôme Depaquit; Anna-Bella Failloux (Public Library of Science (PLoS), 2023)
West Nile virus (WNV) and Usutu virus (USUV) are two arthropod-borne viruses that circulate in mainland France. Assessing vector competence has only been conducted so far with mosquitoes from southern France while an increasingly active circulation of WNV and USUV has been reported in the last years. The main vectors are mosquitoes of the Culex genus and the common mosquito Culex pipiens. Here, we measure the vector competence of five mosquito species (Aedes rusticus, Aedes albopictus, Anopheles plumbeus, Culex pipiens and Culiseta longiareolata) present in northeastern France. Field-collected populations were exposed to artificial infectious blood meal containing WNV or USUV and examined at different days post-infection. We show that (i) Cx. pipiens transmitted WNV and USUV, (ii) Ae. rusticus only WNV, and (iii) unexpectedly, Ae. albopictus transmitted both WNV and USUV. Less surprising, An. plumbeus was not competent for both viruses. Combined with data on distribution and population dynamics, these assessments of vector competence will help in developing a risk map and implementing appropriate prevention and control measures.